Antioxidant and Antistaphylococcal Activity of Topical Fucoidan Gel from Sargassum oligocystum Montagne - Richie Bayuran (Philippine Association of Institutions for Research, Inc., 2019)
Brown seaweed is one of the algal species that has been used as food, a source of nutritional supplements, and formulated for therapeutic and cosmetic purposes. This study evaluated the antioxidant and antistaphylococcal activities of topical fucoidan gel (TFG) from the Sargassum oligocystum. A completely randomized design was used, and the experimental protocol includes extraction, lyophilization, and characterization, quality testing, and biological assay. Physicochemical tests suggested that the lyophilized fucoidan is comparable with the properties of pharmaceutical-grade fucoidan. FTIR characterization revealed that fucoidan spectra contain the key functional groups, the sulfate groups, and polysaccharide chains. The formulated topical fucoidan gel also conforms to the selected minimum standards conducted for semi-solid preparation. Analysis of variance of antioxidant and antistaphylococcal assays showed that there was a significant difference in the median inhibitory concentration (IC50) and inhibitory zone (IZ) among treatments at the p<.01 respectively. Scheffe test confirmed that the IC50 of treatment pairs Ascorbic Acid (AA) -TGF, AA-Lyophilized Fucoidan (LF), and TFG-LF were insignificant, which means they are comparable. Consequently, the IZ of Mupirocin 15ug/ml and TFG 45ug/ml has no significant difference, and its inhibitory zones on S. aureus are comparable. Thus, the results suggested that lyophilized fucoidan from S. oligocystum is a potential alternative antioxidant and antistaphylococcal agent.